Harmonic Response Analysis of Strut Fin on Planar Motion Mechanism - Kusnindar Priohutomo; Danang Ariyanto (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
In a material selection design that will be used is one important step. Because by selecting the right material with the appropriate material properties, it can be seen the harmonic response value of a structure. By knowing the value of harmonic response in a structure, at the time of testing can avoid damage to the structure. In this study the material used for Fin Planar Motion Mechanism (PMM) is Stainless Steel 304 (SS 304). To calculate the harmonic response, the SPSS method is used. From the research results in the range 1-100 Hz the displacement value is still below the limit with a maximum value of 2.50E-12 mm and a maximum stress value of 2.95E-05 Pa.